Linguaggio e violenza in Hannah Arendt: una prospettiva retorica / Language and violence in Hannah Arendt: a rhetorical perspective - Serra, Mauro (Rivista Italiana di Filosofia del Linguaggio, 1970)
Arendt’s thought appears promising to investigate the relationship between language and violence. On the one hand, she devoted a deep reflection to the theme of violence, which culminated in the 1969 text On violence. On the other, she developed a ‘communicative conception of power’ in which the eminently linguistic practice of persuasion and the conflict (agōn) between different opinions constituted the foundation of political action. Despite this, however, for Arendt language and violence remain two substantially distinct phenomena. This paper will try to show why this happens and to suggest that another theoretical path would have been possible by attributing a different role and nature to rhetoric.